Abordagem das funções exponencial e logarítmica no ensino médio e superior - Pinheiro, Ana Maria (2021)
This dissertation aims to study a methodological approach of Exponential and Logarithmic Functions in a conceptual and graphic perspective in secondary and higher education. Aiming to analyze the approaches made in secondary and higher education of exponential and logarithmic functions. First, we'll show a brief history about the emergence of exponential and logarithmic functions, created to simplify calculations and to better understand their applications. Then, we will study the definitions, properties, theorems and demonstrations of these functions in secondary and higher education. To finish this study, some applications on exponential and logarithmic functions were highlighted.